Peningkatan Speed dan Agility dengan Penggunaan Latihan 40 Yard Sprint dan A-Movement - Govenda, Roky Dian; Hariyanto, Agus; Herdyanto, Yonny (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2020)
Speed and agility are two important components in sports. Both are commonly used to indicate an athlete's physical fitness in training. Therefore, special training is needed to improve speed and agility. Exercise is an activity that is carried out repeatedly to achieve better physical, mental, and psychological enhancement. The type of exercise used varies for each physical condition that needs to be improved. This study examined the use of 40-yard sprint and A-movement exercise to improve speed and agility. The research design is a quasi- experimental study with participants consist of 30 male students of SMAN 1 Banyuwangi, aged 16-18 years old, who are members of futsal extracurricular club. The training program was conducted for 6 weeks with a frequency of 3 meetings every Sunday. The obtained results of statistical calculations were normal and homogeneous data. Calculation of the effect test with Î± = 5% obtained significance values of 0.00 for speed and 0.004 for agility. Based on these results, it can be concluded that the 40-yard sprint and A-movement exercise combined are effective to improve speed and agility. Further research is suggested to find out which type of exercise is better at increasing speed and agility.